The Suitability of the Real Costs Against the Price of the Ina-Cbg's on Patients Prolonged Labour at the Regional General Hospital Pandan Arang Boyolali - Pertiwi Awilda (Journal of Advanced Pharmaceutical Research Sciences and Sustainability (JAPRSS), 2026)
Background. Prolonged labour defrayel was regulated in the INA-CBG’s rates. Purpose. The purpose of this research is to know the difference real costs against the price of the INA-CBG's and know the factors which influence the real costs in patients prolonged labour at the regional genral hospital Pandan Arang Boyolali. Method. The research was on analytic observation research used a cross-sectional design according to the hospital perspective and data collection method was retrospectively. The data of this research were quantitative data. Analysis of suitability of real cost with INA-CBG's used t-test, one being an analysis of the factors that affect the real costs used bivariate correlation test. Results. The study result showed that were difference between of real costs to the INA-CBG's rates on severity I on a class of treatments 1, 2 and 3 showed positive values, as for the difference obtained class 1 Rp. 3.195.800, class 2 Rp 15.634.812 and class 3 Rp. 9.762.782. On the severity II class of treatments 3 showed positive difference amounted Rp. 1.567.806. Conclusion. The difference were shown the positive difference, were indicates the total real costs lower than INA-CBG's rate. The factors was affected the real costs of prolonged labour was LOS.